Pengaruh Profitabilitas, Kebijakan Hutang Dan Keputusan Investasi Terhadap Nilai Perusahaan(Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2014-2015) - Augustin, Chendy Nur; , Drs. Farid Wajdi, MM., Ph.D (2017)
This study aims to determine whether Profitability, Debt Policy and Investment Decisions affect the Company's value in the companies listed in Indonesia Stock Exchange in 2014 - 2015. The population in this study are all manufacturing companies listed in Indonesia Stock Exchange in 2014-2015 . The research sample as many as 16 companies. The data used is secondary data. The method of analysis used in the study is multiple linear regression. The analysis showed that the significant effect on the profitability of the Company Values. While the Debt Policy and Investment Decisions no significant effect on the Company Values.